Pivot Templators’ Challenges and Training: Insights from a Survey Study with Subtitlers and Subtitler Trainers - Pięta, Hanna; Valdez, Susana; Torres-Simón, Ester; Menezes, Rita (Íkala, Revista de Lenguaje y Cultura, 2023)
Given the increase of non-English audiovisual content, translating through pivot templates is increasingly common. Yet, pivot templates have attracted scant scholarly attention. Several factors remain unclear. Among the first factors are the questions of who creates pivot templates, from what languages are they translated, into what languages are they translated, and what audiovisual products and channels are they for? Secondly, what are the challenges involved in the creation of templates? The third factor would be whether there is any training available for pivot template creators, and whether this training is effective. To provide more clarity on these issues, we distributed a questionnaire and elicited replies from 100 pivot templators and 75 subtitler trainers based in Europe. The results indicate that most pivot templators translate into English as L2. Because of this, diverse difficulties arise. Training in pivot template making seems rare, especially compared to training in subtitling in general. The training that is offered comes mainly from the industry and not academia. This is problematic for various reasons: (a) the former does not typically cover issues related to subtitler ethics or the sustainability of the profession, and (b) translator training and professional codes of conduct eye L2 translation with suspicion. Drawing on the respondents’ insights, we argue that much can be gained from teaching non-English-language native speakers how to create English-language templates.